1996
DOI: 10.1006/brln.1996.0043
|View full text |Cite
|
Sign up to set email alerts
|

Microstates in Language-Related Brain Potential Maps Show Noun–Verb Differences

Abstract: Brain processing of grammatical word class was studied analyzing event-related potential (ERP) brain fields. Normal subjects observed a randomized sequence of single German nouns and verbs on a computer screen, while 20-channel ERP field map series were recorded separately for both word classes. Spatial microstate analysis was applied, based on the observation that series of ERP maps consist of epochs of quasi-stable map landscapes and based on the rationale that different map landscapes must have been generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(64 citation statements)
references
References 43 publications
(54 reference statements)
3
61
0
Order By: Relevance
“…Coordinates in mm after Talairach and Tournoux (1988); origin at anterior commisure; X left (2) to right (1); Y posterior (2) to anterior (1); Z inferior (2) present study allowed the discrimination of sequential brain microstates as basic elements of brain information processing (Koenig and Lehmann, 1996;Koenig et al, 1998;Lehmann et al, 1998). The two microstates at 132±196 ms and at 196±272 ms after stimulus onset were systematically in¯uenced by the subjects' affective attitude towards the face images (assessed after the experiment).…”
Section: Temporal Aspects Of the Personality-modulated Faceelicited mentioning
confidence: 87%
See 3 more Smart Citations
“…Coordinates in mm after Talairach and Tournoux (1988); origin at anterior commisure; X left (2) to right (1); Y posterior (2) to anterior (1); Z inferior (2) present study allowed the discrimination of sequential brain microstates as basic elements of brain information processing (Koenig and Lehmann, 1996;Koenig et al, 1998;Lehmann et al, 1998). The two microstates at 132±196 ms and at 196±272 ms after stimulus onset were systematically in¯uenced by the subjects' affective attitude towards the face images (assessed after the experiment).…”
Section: Temporal Aspects Of the Personality-modulated Faceelicited mentioning
confidence: 87%
“…Originally, predetermined window sizes were used (Lehmann and Skrandies, 1984;Lehmann, 1987). In the present study, a data-driven approach is used so that window size preselection is avoided (Koenig and Lehmann, 1996;Koenig et al, 1998). This approach involves three basic steps.…”
Section: Microstate Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, their studies have shown that these microstates are associated with different modes of spontaneous thoughts [270] or with spontaneous visual imagery, or abstract thinking [271].…”
Section: O1mentioning
confidence: 99%